Associação da Moringa oleifera e do sulfato de alumínio com o processo de eletrocoagulação para a redução dos parâmetros físico-químicos da água - Iwamura, Vinícius Cavani (2016)
Due to the importance of water to human life, we must always be looking for new ways to ensure the quality of this resource for human consumption, to increase efficiency and reduce process costs. An alternative method for treating conventional water is the electrocoagulation process that uses electricity to oxidize the electrodes reactor, reacting with dirty water particules causing them to coagulate. Another way to diversify the water treatment is to use different types of natural coagulants such as Moringa oleifera having a cationic protein with high acceleration capability of the coagulation process. Another possibility would also be to insert this natural chemical coagulant to coagulant already widespread and used in water treatment stations. Therefore, this study aims to evaluate the association of coagulants Moringa oleifera and aluminum sulfate with the electrocoagulation process, seeking to identify the electrocoagulation process becomes more efficient or not with the aid of these elements. For this, a reactor was constructed using four iron electrodes, a power source of 12 V and 0.20 A of electric current. The parameters analyzed were: pH, temperature, turbidity, apparent color, electrical conductivity and series of solids. In order to compare the efficiency of processes were performed three types of treatments, electrocoagulation associated with Moringa oleifera (T1), electrocoagulation associated with aluminum sulphate (T2) and only electrocoagulation (T3), also varying the concentration of the coagulant, It has used assays with a concentration of 30 mg.L-1 and 50 mg.L-1 for Moringa oleifera and 25 mg.L-1 and 50 mg.L-1 for aluminum sulfate. At the end of the test it was concluded that the electrocoagulation process associated Moringa oleifera is the most efficient treatments in relation removing turbidity and apparent color, reaching 92% and 47%, respectively. For pH electrocoagulation associated Moringa oleifera showed an increase of considerable pH, reaching 11, the other treatments maintained the pH in the range between 7 and 9. For the total solids association electrocoagulation with Moringa oleifera was not so advantageous obtaining a maximum efficiency of 11% removal (C1), treatment using only electrocoagulation was able to reduce 24% of the total solids in water, and the association of electrocoagulation with aluminum sulphate had the highest removal efficiency of the three types of treatment, removing up to 54% (C2) of the total solids present in the water. The test results for fixed and volatile solids were inconclusive.